Irisin reshapes bone metabolic homeostasis to delay age-related osteoporosis by regulating the multipotent differentiation of BMSCs via Wnt pathway - Xing, Shangman; Ma, Yifan; Song, Bing; Bai, Min; Wang, Kexin; Song, Wenjing; Cao, Tingting; Guo, Chao; Zhang, Yanying; Wang, Zhandong; Wang, Yongfeng (Frontiers in Molecular Biosciences, 2025)
IntroductionBone aging is linked to changes in the lineage differentiation of bone marrow stem cells (BMSCs), which show a heightened tendency to differentiate into adipocytes instead of osteoblasts. The therapeutic potential of irisin in addressing age-related diseases has garnered significant attention. More significantly, irisin has the capacity to enhance bone mass recovery and sustain overall bone health. Its mechanism of action in preventing osteoporosis has generated considerable interest within the research community. Nonetheless, the targeting effect of irisin on age-related osteoporosis and its underlying molecular biological mechanisms remain unclear.MethodsThe specific role of irisin in osteogenic-adipogenic differentiation in young or aging BMSCs was evaluated by multiple cells staining and quantitative real-time PCR (RT-qPCR) analysis. RNA-seq and protein Western blotting excavated and validated the key pathway by which irisin influences the fate determination of aging BMSCs. The macroscopic and microscopic changes of bone tissue in aging mice were examined using Micro-computed tomography (Micro-CT) and morphological staining.ResultsIt was noted that irisin affected the multilineage differentiation of BMSCs in a manner dependent on the dosage. Simultaneously, the Wnt signaling pathway might be a crucial mechanism through which irisin sustains the bone-fat balance in aging BMSCs and mitigates the decline in pluripotency. In vivo, irisin reduced bone marrow fat deposition in aging mice and effectively alleviating the occurrence of bone loss.ConclusionIrisin mediates the Wnt signaling pathway, thereby influencing the fate determination of BMSCs. In addition, it is essential for preserving metabolic equilibrium in the bone marrow microenvironment and significantly contributes to overall bone health. The findings provide new evidence for the use of iris extract in the treatment of age-related osteoporosis.